Overexpression of FSP1 Ameliorates ferroptosis via PI3K/ AKT /GSK3β pathway in PC12 cells with Oxygen-Glucose Deprivation/Reoxygenation - Yonghui Wu; Haoyu Shi; Jie Zheng; Yang Yang; Xuejiao Lei; Xiao Qian; Jie Zhu (Heliyon, 2023)
After ischemia and reperfusion (I/R), nerve cell damage is a pathogenic process that involves numerous molecular processes. In the last ten years, one new classification of programmed cell death is ferroptosis. More recent research has demonstrated that ferroptosis has a role in a variety of neurological disorders, including stroke, cancer, and neurodegenerative illnesses. Ferroptosis suppressor protein 1 (FSP1) plays a significant role in inhibiting ferroptosis. The purpose of this work is to determine how overexpression of FSP1 affects the ferroptosis of PC12 cells under the condition of oxygen-glucose deprivation/reoxygenation (OGD/R). The expression of FSP1 was regulated by lentivirus transfection technology. Western blot and immunofluorescence were used to measure protein levels related to ferroptosis and the PI3K/AKT/GSK3β signal pathway. Determine cell viability using the appropriate kit. Mitochondrial structural morphology was checked by transmission electron microscopy in PC12 cells. Reactive oxygen species (ROS) and Malondialdehyde (MDA) were quantified using the relevant kits. OGD/R induced ferroptosis in PC12 cells, however, FSP1 overexpression reverses ferroptosis and promotes cell viability, lowering ROS and MDA content. The expression of FSP1 decreased in OGD/R0h and OGD/R6h and rebounded in OGD/R24h and OGD/R48h. During the processes of OGD/R-induced ferroptosis, FSP1 overexpression significantly stimulated PI3K/AKT/GSK3β pathway, but LY294002 weakens the protective effect of FSP1 overexpression. Our outcomes demonstrate that overexpression of FSP1 markedly enhances the ability to resist ferroptosis via the PI3K/AKT/GSK3β pathway. The above results may provide a new preliminary lead for the treatment of the cerebral ischemia-reperfusion injury.